The Difference Of Effectiveness way to Consume Iron tablets toward haemoglobin level changes to pregnant women in second trimester at the Sindang Barang community health center in 2017 - Triswanti; Maghfiroh, Tri (Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Giving iron tablets together with drinking orange juice can increase hemoglobin levels higher than administering iron tablets alone Purpose: This study aims to examine the differences in the effectiveness of taking iron tablets against changes in hemoglobin levels in second trimester pregnant women at Sindang Barang Bogor Community Health Center. Methods: Quasi experimental research with Pretest-Posttest Control Group Design. The sample is divided into two groups, namely the intervention group and the control group. The intervention group was given iron tablets simultaneously by drinking orange juice for 30 days. Result: The provision of iron tablets simultaneously drinking with lemon juice water is more effective than the provision of iron tablets simultaneously drinking with lemon juice water is more effective than the provision of iron tablets simultaneously drink with water in pregnant women second trimester. Conclusion: By giving vitamin C in the form of tablets or orange juice or foods or tablets of vitamin C can increase the absorption og iron pregnant women